PROSES PENGERINGAN NPK BERDASARKAN EVALUASI ROTARY DRYER DAN KADAR AIR NPK DI PT. PETROKIMIA GRESIK - Guluh Fauziah Marintika; Lia Cundari; Farid Hayu Kurniawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Drying is an important process in the production of NPK fertilizers. The average NPK water content in August 2021 – January 2022 was 1.64%, still exceeding a good NPK water content of < 1.5%. The high NPK moisture content resulted that review are needed in drying process through rotary dryer evaluation and observation by creating multiple linear regression math. The average thermal efficiency is calculated based on the actual data, which is 73%, do not decrease significantly and still close to the value of the design data of 90%. The mathematical equation obtained is Y1 = 114.9292 + 0.000338X1 + 0.0439062X2 -1.711792X3 -0.3749378X4 with a regression coefficient of 0.8657472. Factors that affect the NPK fertilizer water content are the air temperature of dryer, the flow rate of incoming NPK water mass, the flow rate of NPK mass and the flow rate of air dryer mass.